Assessment of Risk Factor for Developing Acute Kidney Injury in the Setting of Acute ST Elevation Myocardial Infarction (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: An acute kidney injury (AKI) is a recognized complication in patients with ST elevationmyocardial infarction (STEMI) by several mechanisms and it adversely affects morbidity and mortality onlong-term bases (1, 2, and 3). Few studies have investigated which patients with STEMI are at risk of developingAKI (6), and this study is aiming to do this assessment.Patients and Methods: We enrolled patients with STEMI who were admitted to the CCU. KDIGOdefinitions was utilized to search for development of AKI in these patients throughout their stay in theCCU (their baseline serum creatinine was measured and traced daily thereafter; and their urine output wasmonitored). Common epidemiological and some relevant medical parameters were recorded for all patients.Results and conclusion: low baseline systolic blood pressure, ejection fraction % and estimated glomerularfiltration rate (eGFR); in addition to use of diuretics; are the major risk factors for the development of AKIin the setting of STEMI.
Keywords: acute kidney injury, ST elevation myocardial infarction